Testing the theoretical consistency of stated preferences for tropical wildlife conservation - Sian Morse-Jones; Ian Bateman; Andreas Kontoleon; Silvia Ferrini; Neil Burgess (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2010)
In this paper, we report the results of an online choice experiment designed to test the theoretical consistency of stated preferences for a complex predominantly non-use good. Our case study concerns the values held by UK residents for the conservation of wildlife in the Eastern Arc Mountains in Tanzania, part of the Eastern Afromontane biodiversity hotspot. Theoretical consistency is assessed through tests of value sensitivity to the scope of the scheme, ordering effects and (more unusually) the presence of substitutes. Critically, we find that 'substitution effects' may account for apparent insensitivity to scope. We also find some evidence that preferences are invariant to the presentation order. Our results highlight the importance of incorporating information about substitutes into the valuation process since welfare estimates may otherwise be overstated.
Keywords: 330; environmental valuation; choice experiment; scope tests; substitution effects; order effects; Offenbarte Präferenzen; Willingness to pay; Substitutionseffekt; Umweltökonomik; Wildtierschutz; Test; Kamerun